The Mechanism of Hydrogen Evolution by Chlamydomonas moewusii - Healey, F. P. (1970)
Using manometric techniques, H(2) evolution in both darkness and light has been studied in the green alga, Chlamydomonas moewusii. Hydrogen evolution in the dark is accompanied by the release of only CO(2) in manometrically detectable amounts. It is depressed by dark starvation and inhibited both by monofluoroacetic acid and by uncouplers of phosphorylation. This evidence suggests that the reaction is dependent on oxidative carbon metabolism for reductant and phosphorylation for energy to raise the reductant to a redox potential capable of reducing H(+). Photoevolution of H(2) is also accompanied by the release of only CO(2). It is depressed by dark starvation and stimulated by acetate or a period of photosynthesis. Monofluoroacetic acid causes complete inhibition, while 3-(3,4-dichlorophenyl)-1,1-dimethylurea causes no or only slight inhibition. These results indicate that oxidative carbon metabolism is the source of reductant for the reaction. Photoevolution of H(2) does not show Emerson enhancement, and it has an action spectrum peaking at a longer wave length than that of photosynthesis. These characteristics, together with the slight effect of 3-(3,4-dichlorophenyl)-1,1-dimethylurea on the reaction, show that only system I of photosynthetic electron transport is involved in the reaction. Photoevolution of H(2) is stimulated by uncouplers; this indicates that the role of light is not to provide energy by phosphorylation. Rather, the results support an electron flow driven directly by light through system I from reductant produced in oxidative carbon metabolism to a redox potential capable of reducing H(+).